Cranial osteology in mornoticlae (Aves : Coradiformes) - Pascotto, M. C.; Donatelli, Reginaldo José [UNESP] (Wiley-Blackwell, 2003)
Momotidae (motmots) is found throughout Latin America between Mexico and northern Argentina. Given the absence of detailed studies of cranial osteology of Momotidae in the literature, this article presents a comprehensive description of the variation of the cranial osteology in all nine species of Momotidae and compares the results with published studies of other families of Coraciiformes and families in other orders. In addition, the cranial structures described are related to ecological and behavioral aspects of Momotidae. The cranial osteology of Baryphthengus ruficapillus is described in detail and compared with other species of Momotidae. The results indicate the presence in Momotidae of modified cranial structures, among which the most conspicuous are the frontal, lacrimal, squamosal, orbital, and laterosphenoid regions, as well as the palatine, upper jaw, pterygoid, and mandible. (C) 2003 Wiley-Liss, Inc.
Keywords: aves; coraciffornies; Momotidae; cranial osteology; jaw osteology